2020
DOI: 10.1111/ejh.13549
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding and future implications of sepsis‐induced thrombocytopenia

Abstract: Sepsis is a global health burden that needs intensive medical care. Thrombocytopenia in sepsis is well known to increase morbidity as well as mortality. Several studies have been performed both in animal models and in humans to understand the mechanism by which sepsis causes thrombocytopenia. Recent studies have shown that inhibiting thrombocytopenia improves outcomes in sepsis patients. Understanding these mechanisms to identify targets in use of newer treatment modalities besides using resuscitation measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…27 Because the GPIb-IX-V receptor membrane complex plays a piv- tide inhibitor and discovered that the process of lipopolysaccharideinduced thrombocytopenia in sepsis was attenuated, while the sepsis mortality of mice expressing a functionally deficient mutant of GPIb-IX was significantly decreased. 28 These findings suggest that targeting GPIb-IX-V could be a possible prospect for managing endotoxemia and sepsis 29 and with relevance to the present study, inherited variants in GP1BA or GP1BB may protect against death from sepsis and thus provide a survival advantage. 28 In conclusion,…”
Section: Re Sults and Discussionsupporting
confidence: 63%
“…27 Because the GPIb-IX-V receptor membrane complex plays a piv- tide inhibitor and discovered that the process of lipopolysaccharideinduced thrombocytopenia in sepsis was attenuated, while the sepsis mortality of mice expressing a functionally deficient mutant of GPIb-IX was significantly decreased. 28 These findings suggest that targeting GPIb-IX-V could be a possible prospect for managing endotoxemia and sepsis 29 and with relevance to the present study, inherited variants in GP1BA or GP1BB may protect against death from sepsis and thus provide a survival advantage. 28 In conclusion,…”
Section: Re Sults and Discussionsupporting
confidence: 63%
“… 22 In critically ill patients, the commonest etiology for thrombocytopenia is sepsis, caused by multiple mechanisms, such as immune-mediation, sequestration of platelets, interaction between platelet receptors, and as a part of disseminated intravascular coagulation (DIC). 23 Raised INR is common in critically ill and is caused by many conditions, such as liver disease, DIC, vitamin K deficiency, inherited deficiency coagulation factors due to production defects, etc. 24 Coagulopathy and its causes in pediatric patients have been extensively reviewed by Parker.…”
Section: Discussionmentioning
confidence: 99%
“…During infection, thrombocytopenia occurs rapidly due to the extensive platelet consumption that follows the release of immunomodulatory agents and the interaction of platelets with neutrophils to form neutrophil extracellular traps 73 . This process may have severe clinical consequences, including increased mortality from loss of vascular integrity, hemorrhage, and even septic shock 74 . It is followed by a quick regeneration of platelets to counteract inflammation‐induced thrombocytopenia.…”
Section: Iron and Platelets: Clinical And Mechanistic Aspects Iron Deficiency And Plateletsmentioning
confidence: 99%
“…73 This process may have severe clinical consequences, including increased mortality from loss of vascular integrity, hemorrhage, and even septic shock. 74 It is followed by a quick regeneration of platelets to counteract inflammation-induced thrombocytopenia. Haas et al have shown that inflammation drives efficient cell cycle activation and maturation of stem-like megakaryocyte committed progenitors that rapidly replenishes the platelet pool during acute inflammation.…”
Section: Functional Iron Deficiencymentioning
confidence: 99%